Toxoplasma gondii infection in local ayam kampung in areas of Selangor and Melaka - Abdul Rahman, Mohammad Sabri (2015)
Toxoplasmosis is a worldwide zoonosis caused by the protozoa Toxoplasma gondii which affects human and animals. Local Ayam Kampung or free-range chickens have recently been reported to be important in the epidemiology of toxoplasmosis. This study determines the presence and common sites of T. gondii infection and related tissue changes using serological and histopathological methods, respectively. A total of 50 serum samples from local Ayam Kampung (Gallus domesticus) from Selangor (20 chickens from four farms) and Melaka (30 chickens from six farms) were collected and analyzed by using serological kits. T. gondii antigen was detected in 20% (Selangor-30%; Melaka-13%) samples using ELISA test and anti-T. gondii antibody was detected in all positive samples from ELISA using the indirect haemagglutination test (IHAT). From the histopathological examination, cysts and tissue changes such as inflammation and degeneration (necrosis) were observed in 18% (9 chickens) of brain samples, 22% (11 chickens) of liver samples and 10% (5 chickens) of spleen samples. The results indicate that T. gondii tend to localize in the liver more often than in other tissues. This is the first report of T. gondii infection in local Ayam Kampung in Malaysia.